2a(b-2c)-3b(2a+3c)=

Simple and best practice solution for 2a(b-2c)-3b(2a+3c)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2a(b-2c)-3b(2a+3c)= equation:


Simplifying
2a(b + -2c) + -3b(2a + 3c) = 0
(b * 2a + -2c * 2a) + -3b(2a + 3c) = 0
(2ab + -4ac) + -3b(2a + 3c) = 0
2ab + -4ac + (2a * -3b + 3c * -3b) = 0
2ab + -4ac + (-6ab + -9bc) = 0

Reorder the terms:
2ab + -6ab + -4ac + -9bc = 0

Combine like terms: 2ab + -6ab = -4ab
-4ab + -4ac + -9bc = 0

Solving
-4ab + -4ac + -9bc = 0

Solving for variable 'a'.

Move all terms containing a to the left, all other terms to the right.

Add '9bc' to each side of the equation.
-4ab + -4ac + -9bc + 9bc = 0 + 9bc

Combine like terms: -9bc + 9bc = 0
-4ab + -4ac + 0 = 0 + 9bc
-4ab + -4ac = 0 + 9bc
Remove the zero:
-4ab + -4ac = 9bc

Combine like terms: 9bc + -9bc = 0
-4ab + -4ac + -9bc = 0

Factor out the Greatest Common Factor (GCF), '-1'.
-1(4ab + 4ac + 9bc) = 0

Ignore the factor -1.

Subproblem 1

Set the factor '(4ab + 4ac + 9bc)' equal to zero and attempt to solve: Simplifying 4ab + 4ac + 9bc = 0 Solving 4ab + 4ac + 9bc = 0 Move all terms containing a to the left, all other terms to the right. Add '-9bc' to each side of the equation. 4ab + 4ac + 9bc + -9bc = 0 + -9bc Combine like terms: 9bc + -9bc = 0 4ab + 4ac + 0 = 0 + -9bc 4ab + 4ac = 0 + -9bc Remove the zero: 4ab + 4ac = -9bc The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined. The solution to this equation could not be determined.

See similar equations:

| 125-216c^3=0 | | -3(2t-2)+4t=3t-6 | | 186-7x=38x+16 | | 8x-5=6x-1 | | 4x^3-12x^2+4x+4=0 | | (x/(x^2-x-6))-(x/(x^2-7x+12)) | | n+23=40 | | 2x+(3)/(4)=3x-(3)/(4) | | 0.12(y-9)+0.16y=0.18y-0.01(60) | | 5/6(12-5b)=35 | | 3a(b+c)+2b(a+c)-c(2a+3b)= | | 5x+17-4x=-8-11 | | x^2+4x=-40 | | (2(y-3))/3=-3y | | (4x+16)/(8)=2x-1 | | -3-11=9x+15-8x | | (4(y-5))/3=-4y | | -x-7y=-18 | | 2-5i=-x+10yi | | -9x+5+10x=-11+13 | | n-12=24 | | (7/2)+(5/2y)=2y-3 | | y=3(3)-9 | | 176-4x=23x+17 | | 0.17-0.01(x+2)=0.03(3-x) | | 9(x+1)-1=3x+6(1+x) | | 5c-7c=(-32) | | 8+3x=24+14 | | 18a-45b-9c= | | A-x=3a | | (x/4)-1=(x/9)+4 | | 4(x-5)=2x+25 |

Equations solver categories